The Construction and Transcultural Dissemination of Negative Images of Jews in a French Thirteenth-Century Illuminated Psalter Made for a Danish Reader - Vidas, Marina (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2018)
Marina Vidas: The Construction and Transcultural Dissemination of Negative Images of Jews in a French Thirteenth-Century Illuminated Psalter Made for a Danish Reader The article is concerned with a thirteenth-century de luxe Psalter (London, British Library, MS Additional 17868) produced in France after 1253. It provides an overview of the relevant literature on the London Psalter, a full description of the textual and pictorial components of the manuscript, including a detailed analysis of the Calendar and Litany, as well as reasons for identifying the intended reader as Danish (rather than French, as has been presumed in earlier scholarly literature). A lengthy and detailed analysis is undertaken of the mostly negative manner in which Jews are represented in the Prefatory Cycle miniatures and Psalter section of the manuscript. It is argued that the image of the Jew in the Prefatory Cycle is shaped by pictorial tradition and the then-current negative perception of Jewish usury while in the Psalter section the depictions of Jews were constructed in response to adjacent texts and to nearby images. It is suggested that the interplay between words and images provided a mnemonic tool for the reader but also reinforced widely-held stereotypes of Jews, for example about Jewish enmity toward Christ. Also presented and discussed is French iconography, including pejorative images of Jews and Judaism, which was assimilated and appropriated in Medieval Danish churches. It is concluded that the images would have shaped the reader’s experience of the text and perception of members of the Jewish faith, centuries before the establishment of Jewish communities in this part of Europe.